2015
DOI: 10.1002/jsfa.7255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound treatment on the wet heating Maillard reaction between mung bean [Vigna radiate (L.)] protein isolates and glucose and on structural and physico‐chemical properties of conjugates

Abstract: Ultrasound-assisted wet heating Maillard reaction between MBPIs and glucose could be a promising way to improve functional properties of MBPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 50 publications
(81 reference statements)
5
49
0
Order By: Relevance
“…7 also showed that the H 0 values of conjugates obtained by ultrasound treatment were all significantly (p < 0.05) higher than that of WPI and increased with the increase in reaction time. C. Li, Huang, et al (2014) and Wang et al (2016) also confirmed that the protein-saccharide conjugates prepared by ultrasound treatment exhibited higher H 0 values than native protein. It may because that the cavitation induced by ultrasound treatment could expose some of the hydrophobic groups initially buried in the interior of protein molecules to the surface and thus increase the H 0 of protein (Zhang et al, 2014).…”
Section: Surface Hydrophobicity (H 0 ) Analysismentioning
confidence: 63%
See 2 more Smart Citations
“…7 also showed that the H 0 values of conjugates obtained by ultrasound treatment were all significantly (p < 0.05) higher than that of WPI and increased with the increase in reaction time. C. Li, Huang, et al (2014) and Wang et al (2016) also confirmed that the protein-saccharide conjugates prepared by ultrasound treatment exhibited higher H 0 values than native protein. It may because that the cavitation induced by ultrasound treatment could expose some of the hydrophobic groups initially buried in the interior of protein molecules to the surface and thus increase the H 0 of protein (Zhang et al, 2014).…”
Section: Surface Hydrophobicity (H 0 ) Analysismentioning
confidence: 63%
“…1B showed that with the increase of ultrasound power, the DG value increased first and then decreased sharply. The max DG value was obtained at 500 W. Wang, et al (2016) reported that the DG of bean protein isolates (BPI) with glucose increased from 150 to 300 W, but decreased at 450 W. Due to its functions of mechanical mass transfer, heating and cavitation, ultrasound was able to support more energy and free amino groups for the process of graft reaction.…”
Section: Effect Of Ultrasound Power On Graft Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be the reason why conjugates showed lower H 0 index results and why a higher degree of glycation caused the index results to reduce more quickly. However, a few studies found that the glycated proteins obtained by classical wet heating or by an ultrasound‐assisted Maillard reaction showed higher H 0 index readings than the control proteins . During incubation and the Maillard reaction there were two effects on H 0 : (i) the incubation exposed hydrophobic groups because the protein was partially denatured by the heating, so H 0 increased; (ii) glycosylation decreased H 0 because the hydrophilic groups of the polysaccharide (or mono, di, or oligosaccharide) were attached to the protein surface and increased the hydrophilic behavior .…”
Section: Resultsmentioning
confidence: 99%
“…High temperatures required for roasting can partially denature, aggregate and modify protein structures, including glycation of lysine and free amines, resulting from Maillard reactions (Walker & Kochhar, 1982;Sun-Waterhouse et al, 2014;Wang et al, 2016). Such protein modifications may reduce the potential number of tryptic peptides generated during the protein digestion step, carried out prior to LC-MS/MS, potentially leading to an under-estimation of the relative abundance of these proteins, compared to raw or non-roasted samples.…”
Section: Effect Of Roasting On Protein Composition and Relative Abundmentioning
confidence: 99%